The Superiority Complex of Drea in the Do Revenge Movie Using Adler’s Theory - Lolang, Benedicta Viorell; Widyaningrum, Agnes (Humanitatis : Journal of Language and Literature, 2025)
This study examines the superiority complex’s behavior in "Do Revenge" to expose the reasons and effects of this behavior, which overrides Drea in the film. The main character’s psychological state is one of the aims. Thus, Alfred Adler’s individual psychology is used in this study to examine the main character’s psychology. The following issues are developed in light of it: (1) Why does Drea decide to take revenge? (2) How does Drea behave to exact her revenge? (3) What effects does Drea’s act of revenge have? This is a descriptive study that uses a context-oriented approach to assess data on Drea’s portrayal as someone who engages in superiority-complex behavior. To identify Drea’s superior behavior, the research process included several steps: first, closely watching the film; then, focusing on her speech and actions; and finally, selecting and analyzing dialogue that reflected a superiority complex and her reasons for acting that way. The film chronicles the life of Drea, who, after her ex uploads and distributes her sex tape, is compelled to take revenge on her friends and her ex out of her heart and to reclaim her identity, thereby denying her admission to her ideal university. In the end, she deliberately wounded some of her friends, including her closest ones, because of the superior attitude that shaped her behavior.